Supporting capacity for research on malaria in Africa. Issue 2 (12th April 2018) - Greenwood, Brian; Gaye, Oumar; Kamya, Moses R; Kibiki, Gibson; Mwapasa, Victor; Phiri, Kamija S; Tagbor, Harry; Terlouw, Dianne; Bates, Imelda; Craig, Alister; Magnussen, Pascal; Theander, Thor G; et al.
Abstract : Substantial progress has been made in the control of malaria in Africa but much remains to be done before malaria elimination on the continent can be achieved. Further progress can be made by enhancing uptake of existing control tools but, in high transmission areas, additional tools will be needed. Development and evaluation of these new tools will require a substantial cadre of African scientists well trained in many different disciplines. This paper describes the activities undertaken by the Malaria Capacity Development Consortium (MCDC) to support the careers of PhD students and postdoctoral fellows undertaking research on malaria at five African universities. A systematic assessment of constraints on PhD training and research support systems was undertaken at each partner African university at the beginning of the programme and many of these constraints were remedied. The success of the programme is shown by the fact that 18 of the 21 PhD students recruited to the programme completed their theses successfully within a 4-year period and that all 27 scientists recruited to the postdoctoral programme were still working in Africa on its completion. The work of the consortium will be continued through Career Development Groups established at each partner university and at an affiliated institution at the University of Nairobi and through the Developing Excellence in Leadership, Training and Science award from the Wellcome Trust made to one of the African partners. Lessons learnt during the MCDC programme may help the planning and execution of other research capacity development programmes in Africa.